2021
DOI: 10.3390/ejihpe11030076
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Degree of Satisfaction with the Health Sciences University Educational Community Regarding the Measures Adopted for the Prevention of COVID-19 in the Academic Year 2020/2021

Abstract: The COVID-19 pandemic caused the start of the academic year 2020/2021 to be conditioned by health and safety regulations. The present research was defined with the aim of analyzing the degree of satisfaction and perceptions on the establishment of bubble groups and pairs and on the use of audiovisual platforms for the development of theoretical and practical university teaching in three degrees of health sciences. A cross-sectional descriptive study was carried out on a representative sample of students and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…The practices of science are at the center of educational researcher [54][55][56][57], especially the practices of science teachers [58,59]. The present study intended to examine the change in science teachers' practices as a result of participating in a professional development program that focuses on NGSS SI activities.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The practices of science are at the center of educational researcher [54][55][56][57], especially the practices of science teachers [58,59]. The present study intended to examine the change in science teachers' practices as a result of participating in a professional development program that focuses on NGSS SI activities.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Regarding hybrid teaching during the academic year 2020-2021, Lorenzo-Lledó et al [32] and Sáiz-Manzanares et al [33] found out students' preferences for the university education mode and identified the difficulties and experiences associated with the received teaching. Another study analyzed the degree of student and teacher satisfaction levels with and their perceptions of establishing bubble groups and pairs, and of using audiovisual platforms to provide theoretical and practical university teaching [34]. However, very few have also considered other university community members' perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…Another problem dealt with was the effects of the recent new teaching method on teachers, showing that it has led to an improvement in their digital skills and professional vision of this method of teaching classes [ 22 ]. Furthermore, research has been conducted on the use of technological tools by university students, and it has been found that it has led to the development of digital skills to improve their professional training, finding in technological tools an exceptional resource for their personal growth [ 26 ]. Online teaching–learning activities during the pandemic period have also been analyzed, leaving evidence that, even though, in the university, there was already a significant infrastructure in place to migrate from face-to-face to online teaching, there was no preparation for the change [ 27 ].…”
Section: Introductionmentioning
confidence: 99%